INTELLIGENT RAIL TRANSPORT MANAGEMENT SYSTEMS - METHODOLOGICAL ESSENCE, GOALS AND TASKS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The use of intelligent systems for the management of railway transport is a current issue related to a number of innovative methods of carrying out freight and passenger transport, traffic management and efficient use of the infrastructure. These systems allow users to be better informed and use them more safely, more coordinated and "smarter". From a methodological point of view, the requirements for these systems are growing, and the technical solutions are developing according to the trends for the development and modernization of the information technologies themselves. In this article, a generalized methodological analysis is made for the requirements, goals and tasks of these systems. The experience of the implemented intelligent systems that are used to manage railway transport is reported, as well as the types of information services that are provided for passengers and cargo.